Metformin suppresses inflammation and apoptosis of myocardiocytes by inhibiting autophagy in a model of ischemia-reperfusion injury - Huang, Kai-yu (Int J Biol Sci, 2020)
Metformin (Met) is a major widely used oral glucose lowering drug for the treatment of type 2 diabetes. It is reported that metformin could regulate autophagy in various diseases of cardiovascular system including in I/R injury, diabetic cardiomyopathy and heart failure. Autophagy plays a controversial role in ischemia/reperfusion (I/R) injury, and this research was performed to explore the cardioprotective effect of Met on I/R injury and discuss the underlying mechanism of autophagy in it. In vivo and in vitro, Met exerted cardioprotection function of decreasing myocardial inflammation and apoptosis with a decrease in the level of autophagy. Moreover, Met significantly inhibited autophagosome formation and restore the impairment of autophagosome processing, which lead to cardioprotection effect of Met. Akt was up-regulated in Met-treated I/R hearts and miransertib, a pan-AKT inhibitor, was able to reverse the alleviating autophagy effect of Met. We demonstrate that Met protects cardiomyocytes from I/R-induced apoptosis and inflammation through down regulation of autophagy mediated by Akt signaling pathway.